Enhancing Plantlet Growth of Vanda floresensis Motes through Acclimatization Chamber, Chitosan Spraying, and Mixed Medium - Rahayu, Enni Suwarsi; Habibah, Noor Aini; Anggraito, Yustinus Ulung; Melati, Dinda; Sinaga, Na Dame Maulibulung; Pa’ee, Furzani (Universitas Negeri Semarang, 2025)
The conservation of Vanda floresensis Motes has been conducted using in vitro techniques and has produced a large number of plantlets. These plantlets require acclimatization, but the optimal method has not yet been found. The aims of the research were to develop an acclimatization protocol by verifying the effectiveness of an acclimatization chamber (AC), chitosan spraying, and mixed medium composition on plantlet growth. The research was conducted in a screen house of Universitas Negeri Semarang, using a factorial randomized block design with three factors. The AC factor consisted of two levels: inside and outside the AC. The chitosan concentration factor consisted of five levels, namely 0.0, 1.5, 3.0, 4.5, and 6.0 ppm. The composition of the mixed medium consisted of three levels. The observed variables included the increase in number, length, and width of the leaf, total chlorophyll content, and wilted leaf. Data were analyzed by ANOVA and Duncan test. It can be concluded that the use of AC, chitosan spraying, and mixed medium composition was effective in increasing leaf growth and total chlorophyll content and reducing wilted leaf. Spraying chitosan of 1.5 - 3.0 ppm with the use of AC and spraying chitosan of 1.5 ppm with a mixed medium of brick pieces, coconut fibre, and tree bark chips with a ratio of 1:2:1 resulted in the highest leaf growth and total chlorophyll content, and the lowest wilted leaf. The results of this study can be used as an acclimatization protocol for orchid propagation for conservation purposes.